2012
DOI: 10.1016/j.epsl.2012.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Riverine particulate material dissolution as a significant flux of strontium to the oceans

Abstract: ISI Document Delivery No.: 078DQ Times Cited: 2 Cited Reference Count: 62 Cited References: ALBAREDE F, 1981, EARTH PLANET SC LETT, V55, P229, DOI 10.1016/0012-821X(81)90102-3 Allegre CJ, 2010, EARTH PLANET SC LETT, V292, P51, DOI 10.1016/j.epsl.2010.01.019 Aller R.C, 2008, J GEOPHYS RES, P113 Aller RC, 1998, MAR CHEM, V61, P143, DOI 10.1016/S0304-4203(98)00024-3 Arsouze T., 2009, BIOGEOSCIENCES, V6, P1 BERNER RA, 1992, GEOCHIM COSMOCHIM AC, V56, P3225, DOI 10.1016/0016-7037(92)90300-8 BLUTH GJS, 1994, GEOCHIM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 62 publications
5
62
1
Order By: Relevance
“…The first field evidence that this mechanism occurs in coastal areas and could account for 6-45% of the marine Sr budget imbalance was recently published [31]. These results confirmed earlier batch experiments that consisted of putting in contact basaltic river particles and seawater and allowed estimating that 2-10% of the Sr originally contained in the particulates was released to seawater during the four months of experiment [30].…”
Section: Competitors For Land-ocean Transferssupporting
confidence: 77%
See 2 more Smart Citations
“…The first field evidence that this mechanism occurs in coastal areas and could account for 6-45% of the marine Sr budget imbalance was recently published [31]. These results confirmed earlier batch experiments that consisted of putting in contact basaltic river particles and seawater and allowed estimating that 2-10% of the Sr originally contained in the particulates was released to seawater during the four months of experiment [30].…”
Section: Competitors For Land-ocean Transferssupporting
confidence: 77%
“…Batch experiments or sequential leaching slightly illuminated the processes by confirming that a fraction of the lithogenic material can be dissolved, releasing some of the elements it contains and contributing to balance their isotopic composition [29][30][31][32]51]. These experiments also showed that secondary phases are rapidly formed, scavenging a large part of most of the released species.…”
Section: (D) What Do the Models Tell Us?mentioning
confidence: 70%
See 1 more Smart Citation
“…Enhancement of weathering rates after deglaciations and tectonic uplifts (Hodell et al, 1989;Krabbenhöft et al, 2010;Porder et al, 2007;Stoll and Schrag, 1998;Taylor and Blum, 1995;Vance et al, 2009) and associated incongruent weathering of silicates (Blum and Erel, 1997), the ease of weathering of island arcs (Allègre et al, 2010), the release of Sr from riverine particulate matter (Jones et al, 2013), and uncertain estimates of the lowtemperature alteration of the oceanic crust (Butterfield et al, 2001;Derry, 2009) and groundwater discharge (Basu et al, 2001) all contribute to the divergence of modeling and observations. Furthermore, while the radiogenic Sr isotope system can provide information about the Sr input fluxes to the ocean it is not suitable for quantification of Sr output fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Like many of the other coupled processes in the water-soil-gas-biota system, a strong link couples physical erosion to the weathering of silicate minerals (Millot et al, 2002;West et al, 2005). Efficient dissolution of silicate mineral particles in seawater may be further evidence of the important link between physical erosion and chemical weathering ( Jeandel et al, 2011;Jones et al, 2013). The significance of this link has been explored from a theoretical point of view within the framework of the geological evolution of the Earth surface (Gabet and Mudd, 2009;West, 2012).…”
Section: Erosionmentioning
confidence: 99%